Mixed occupancy: the crystal structure of scheelite-type LiLu[MoO 4 ] 2 - Hartenbach, Ingo; Hertweck, Robin F. (Acta crystallographica. Section E, Crystallographic communications, 2024)
Coarse colorless single crystals of lithium lutetium bis[orthomolybdate(VI)], LiLu[MoO 4 ] 2 , were obtained as a by-product from a reaction aimed at lithium derivatives of lutetium molybdate. The title compound crystallizes in the scheelite structure type (tetragonal, space group I 4 1 / a ) with two formula units per unit cell. The Wyckoff position 4 b (site symmetry \overline{4}) comprises a mixed occupancy of Li + and Lu 3+ cations in a 1:1 ratio. In comparison with a previous powder X-ray study [Cheng et al. (2015). Dalton Trans. 44 , 18078–18089.] all atoms were refined with anisotropic displacement parameters.